Comparative Effects of Phosphoenolpyruvate, a Glycolytic Intermediate, as an Organ Preservation Agent with Glucose and N-Acetylcysteine against Organ Damage during Cold Storage of Mouse Liver and Kidney. (5th December 2013) - Ishitsuka, Yoichi; Fukumoto, Yusuke; Kondo, Yuki; Irikura, Mitsuru; Kadowaki, Daisuke; Narita, Yuki; Hirata, Sumio; Moriuchi, Hiroshi; Maruyama, Toru; Hamasaki, Naotaka; Irie, Tetsumi
Abstract : We evaluated the usefulness of phosphoenolpyruvate (PEP), a glycolytic intermediate with antioxidative and energy supplementation potentials, as an organ preservation agent. Using ex vivo mouse liver and kidney of a static cold storage model, we compared the effects of PEP against organ damage and oxidative stress during cold preservation with those of glucose or N-acetylcysteine (NAC). Lactate dehydrogenase (LDH) leakage, histological changes, and oxidative stress parameters (measured as thiobarbituric acid reactive substance and glutathione content) were determined. PEP (100 mM) significantly prevented an increase in LDH leakage, histological changes, such as tubulonecrosis and vacuolization, and changes in oxidative stress parameters during 72 h of cold preservation in mouse liver. Although glucose (100 mM) partly prevented LDH leakage and histological changes, no effects against oxidative stress were observed. By contrast, NAC inhibited oxidative stress in the liver and did not prevent LDH leakage or histological changes. PEP also significantly prevented kidney damage during cold preservation in a dose-dependent manner, and the protective effects were superior to those of glucose and NAC. We suggest that PEP, a functional carbohydrate with organ protective and antioxidative activities, may be useful as an organ preservation agent in clinical transplantation.